2012
DOI: 10.1111/j.1751-2980.2012.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Current status and limitations of the newly developed endocytoscope GIF‐Y0002 with reference to its diagnostic performance for common esophageal lesions

Abstract: The low percentage of specificity for the pathologist's diagnosis was considered to be attributed to the low magnification power of the GIF-Y0002. A further increase in the magnifying power of this instrument will be necessary to broaden its clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…However, the specificity of diagnosis by a pathologist who was blinded to the conventional endoscopic view was considerably low (46.7%) because the low magnification power of this ECS prevented any assessment of nuclear abnormality. We concluded that higher‐magnification continuous‐zoom ECS would allow a more precise pathologic diagnosis, and obviate the need for biopsy histology …”
Section: Introductionmentioning
confidence: 90%
“…However, the specificity of diagnosis by a pathologist who was blinded to the conventional endoscopic view was considerably low (46.7%) because the low magnification power of this ECS prevented any assessment of nuclear abnormality. We concluded that higher‐magnification continuous‐zoom ECS would allow a more precise pathologic diagnosis, and obviate the need for biopsy histology …”
Section: Introductionmentioning
confidence: 90%
“…No serious complications of ECS have been reported yet [6] . At present, a standardized endocytoscopic atypia classification system has been described for esophageal squamous cell lesions [2] and colorectal [5] adenomatous lesions.…”
Section: Another Interesting Finding Of the Present Study Is Thementioning
confidence: 99%
“…The dual CCD prototype carries both conventional magnification (× 80) and ultra-high magnification (× 480) abilities, which can be easily interchanged by pushing a button on the endocytoscope [2,6] . The single CCD prototype endocytoscope (CIF-Y0002, EC2 Olympus) has only one lens that can consecutively increase the magnification power from the conventional magnification power to × 380 using a hand lever.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations